2010
DOI: 10.1098/rstb.2010.0030
|View full text |Cite|
|
Sign up to set email alerts
|

Geographical variation in postzygotic isolation and its genetic basis within and between twoMimulusspecies

Abstract: The aim of this study is to investigate the evolution of intrinsic postzygotic isolation within and between populations of Mimulus guttatus and Mimulus nasutus. We made 17 intraspecific and interspecific crosses, across a wide geographical scale. We examined the seed germination success and pollen fertility of reciprocal F 1 and F 2 hybrids and their pure-species parents, and used biometrical genetic tests to distinguish among alternative models of inheritance. Hybrid seed inviability was sporadic in both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
1
50
1
Order By: Relevance
“…In Mimulus, cryptic CMS occurs in crosses of M. nasutus to several M. guttatus populations with distinct mitochondrial haplotypes (C. M. Barr, L. Fishman and A. L. Case 2016, unpublished data) and also in a few within-guttatus hybrids [51], but each CMS type appears restricted to a small geographical area. Similar patterns are seen in other taxa (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In Mimulus, cryptic CMS occurs in crosses of M. nasutus to several M. guttatus populations with distinct mitochondrial haplotypes (C. M. Barr, L. Fishman and A. L. Case 2016, unpublished data) and also in a few within-guttatus hybrids [51], but each CMS type appears restricted to a small geographical area. Similar patterns are seen in other taxa (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on reinforcement in plants are restricted to a few species and found no supporting evidence (Moyle et al, 2004). More recently, attention has been focused on the genetic base of postzygotic isolation in plants (Costa et al, 2007;Skrede et al, 2008;Martin & Willis, 2010). For logistic reasons, studies of postzygotic isolation are generally conducted in simple laboratory environments and, understandably, they tend to focus on intrinsic components of postzygotic isolation (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…In Mimulus guttatus, one of the parental species of M. peregrinus, reduced pollen viability is sometimes expressed in interpopulation crosses (Fishman and Willis 2006;Sweigart et al 2007). Reduced pollen fertility in intraspecific crosses of M. guttatus is thought to arise through Dobzhansky-Muller incompatibilities between populations either from nuclear-nuclear or nuclear-cytoplasmic interactions (Martin and Willis 2010). Mimulus peregrinus could inherit these preexisting genetic incompatibilities from its parental taxa causing lower pollen fertility when independently originated populations are crossed.…”
Section: Interfertility Of Mimulus Peregrinus Of Independent Originmentioning
confidence: 99%
“…On the other hand, independently originated populations may be isolated from each other by postzygotic reproductive barriers due to genetic or chromosomal incompatibilities that either predate the polyploidisation event or evolve subsequently. For example, nuclear-nuclear and nuclear-cytoplasmic incompatibilities within or between species can result in postzygotic isolation barriers among genetically differentiated populations (Levin 2003;Coyne and Orr 2004;Martin and Willis 2010;Burton et al 2013;Lindtke and Buerkle 2015). If genetically distinct parental populations of a given parental taxon give rise to separate polyploids, the derived polyploids may be reproductively isolated upon secondary contact.…”
Section: Introductionmentioning
confidence: 99%